Safely prosperous or really rich : choosing your personal financial heaven - Ruff, Howard J. (Wiley, 2004)
Praise for SAFELY PROSPEROUS or REALLY RICH?. "Howard's brilliant concept that the roads to Prosperity and Riches are very different is very liberating. In most financial books, the author would never do what Howard has done-recount with unflinching honesty the big financial mistakes he and his subscribers have made over the years so readers can avoid the same stumbling blocks and pitfalls. Only a very secure man would have the guts to do that."--Robert Allen. author of Multiple Streams of Income and Nothing Down. "Howard Ruff is back, offering a wealth of powerful new financia